2015
DOI: 10.1038/nn.4001
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signaling in astrocytes from Ip3r2−/− mice in brain slices and during startle responses in vivo

Abstract: Intracellular Ca2+ signaling is considered important for multiple astrocyte functions in neural circuits. However, mice devoid of inositol triphosphate type 2 receptors (IP3R2) reportedly lack all astrocyte Ca2+ signaling, but display no neuronal or neurovascular deficits, implying that astrocyte Ca2+ fluctuations play no role(s) in these functions. An assumption has been that loss of somatic Ca2+ fluctuations also reflects similar loss within astrocyte processes. Here, we tested this assumption and found dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
601
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 442 publications
(661 citation statements)
references
References 50 publications
47
601
2
Order By: Relevance
“…1E) and a greater number of signals ( Fig. 1D) than endfeet or somata, comparable to previous reports with other calcium indicators and in other brain regions (Shigetomi et al 2013;Gee et al 2014;Kanemaru et al 2014;Otsu et al 2015;Srinivasan et al 2015;Tang et al 2015). A previous study has also detected three different populations of GCaMP6s peaks in astrocytes: single peaks, multi peaks, and plateaus (Bonder and McCarthy 2014).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…1E) and a greater number of signals ( Fig. 1D) than endfeet or somata, comparable to previous reports with other calcium indicators and in other brain regions (Shigetomi et al 2013;Gee et al 2014;Kanemaru et al 2014;Otsu et al 2015;Srinivasan et al 2015;Tang et al 2015). A previous study has also detected three different populations of GCaMP6s peaks in astrocytes: single peaks, multi peaks, and plateaus (Bonder and McCarthy 2014).…”
Section: Discussionsupporting
confidence: 91%
“…We specifically examined IP3 signaling and found that, similar to a previous study (Srinivasan et al 2015),…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Thus, it is conceivable that knocking-down or knocking-out of the IP 3 receptors specifically in astrocytes may allow us to study astrocyte silencing. To genetically manipulate this signaling, researchers have used the astrocyte-specific IP 3 receptor-2 (ITPR2) gene knockout mice and found that the astrocyte Ca 2+ responses to neuronal activity are somewhat diminished 47 . However, while Ca 2+ responses in the astrocyte somata may be depend on ITPR2 signaling it appears that Ca 2+ flux in distal fine processes appears to be at least partially ITPR2-independent, mediated by extracellular influx or release from mitochondrial stores 47,48 .…”
Section: Genetic Manipulationsmentioning
confidence: 99%